1992
DOI: 10.1620/tjem.166.417
|View full text |Cite
|
Sign up to set email alerts
|

Pericentric Inversion of Chromosome 9 in Prenatal Diagnosis and Infertility.

Abstract: In order to evaluate the relation between pericentric inversion of chromosome 9 (inv (9)) and clinical problems, the characteristics of inv (9) were investigated on the basis of chromosomal analyses of fetuses and infertile couples. The incidence of such inversion in fetuses with parents having an offspring who suffered from various clinical problems was significantly higher than the basic incidence obtained in fetuses karyotyped by reason of advanced maternal age. In the chromosomal examination of the parents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 18 publications
1
35
1
1
Order By: Relevance
“…Most clinicians have considered inv (9) to be a benign chromosomal polymorphism [23][24][25]. Uehara et al reported that infertile couples with an inv (9) carrier showed a significantly higher incidence of intrauterine fetal death, compared with infertile couples with a translocation carrier or those in which the etiology was unknown [26]. The inv (9) may often cause clinical problems in offspring of the carrier and infertility with unknown mechanisms related to sex [24].…”
Section: Discussionmentioning
confidence: 99%
“…Most clinicians have considered inv (9) to be a benign chromosomal polymorphism [23][24][25]. Uehara et al reported that infertile couples with an inv (9) carrier showed a significantly higher incidence of intrauterine fetal death, compared with infertile couples with a translocation carrier or those in which the etiology was unknown [26]. The inv (9) may often cause clinical problems in offspring of the carrier and infertility with unknown mechanisms related to sex [24].…”
Section: Discussionmentioning
confidence: 99%
“…increased risk of birth of offspring having Down syndrome (Serra et al, 1990;Uehara et al, 1992). Based on those previous reports, it is suggested that the carriers with pericentric inv(12) do not always suffer from clinical problems but have a relatively high risk of infertility or additional chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Boue and Gallano (1984) described that couples with a pericentric inversion ascertained through an infant with unbalanced rearrangement can be considered to be a high risk group for unbalanced offspring. Although pericentric inv(9) is known to be a normal chromosomal variant which does not affect phenotype, this rearrangement has been reported to be related to infertility (Boue et al, 1975;Uehara et al, 1992) and a Vol. 39, No.…”
Section: Discussionmentioning
confidence: 99%
“…Visualized polymorphic variations in the length of the centromeric heterochromatin on the long arms of chromosomes 1, 9 and 16 (1qh+/-, 9qh+/-and 16qh+/-) were documented. Distinct polymorphic variants of the size of satellites (ps+) and lengths of stalks (pstk+) of the acrocentric chromosomes (Akbas et al, 2010;, Rao et al, 2006;, Uehara et al, 1992;Kosyakova et al, 2013;Ganguly and Kadam, 2014) were also recorded. The pericentric inversion of chromosomes 9 was considered as a heteromorphism.…”
Section: Cytogenetic Analysismentioning
confidence: 94%